Writing as Witnessing, Poetry as Agency of Aid: The Five Poems from Typhoon Yolanda Relief Anthologies - Vac Ann C. Dadia (POETIKA, 2020)
The strong typhoon Yolanda (international name: Haiyan), which buffeted the central Philippine region on November 2013 spurred the publication of several relief anthologies, so-called because they were primarily intended to raise funds for the disaster victims. This paper argues that as a distinct method of volunteerism, the poems that comprise the Yolanda relief anthologies are ecopoems which not only bear intrinsic ecological themes that confront an environment in crisis but also embody what Filipino poet Luisa A. Igloria describes as a "work of witness and deep engagement" in a time of climate and humanitarian crisis. In analyzing the five poems from two Yolanda relief anthologies, namely, Agam: Filipino Narratives on Uncertainty and Climate Change and Verses Typhoon Yolanda: A Storm of Filipino Poets, this paper utilizes the theories developed by the Filipino poets who are themselves contributors to these relief anthologies, specifically on how poetry is an act of witnessing and functions as an agency of symbolic aid. The findings contribute to the discourse on ethical literature and thus suggest that the existing brand of Philippine ecopoetry allows for poems that articulate empathic and hopeful agency towards climate-related disaster survivors.